Association of Overlapping Neurosurgery With Patient Outcomes at a Large Academic Medical Center. Issue 6 (20th August 2019) - Agarwal, Prateek; Ramayya, Ashwin G; Osiemo, Benjamin; Goodrich, Stephen; Glauser, Gregory; McClintock, Scott D; Chen, H Isaac; Schuster, James M; Grady, M Sean; Malhotra, Neil R
Abstract: BACKGROUND: Limited data exist on the safety of overlapping surgery, a practice that has recently received widespread attention. OBJECTIVE: To examine the association of overlapping neurosurgery with patient outcomes. METHODS: A total of 3038 routinely scheduled, elective neurosurgical procedures were retrospectively reviewed at a single, multihospital academic medical center. Procedures were categorized into any overlap or no overlap and further subcategorized into beginning overlap (first 50% of procedure only), end overlap (last 50% of procedure only), and middle overlap (overlap at the midpoint). RESULTS: A total of 1030 (33.9%) procedures had any overlap, whereas 278 (9.2%) had beginning overlap, 190 (6.3%) had end overlap, and 476 (15.7%) had middle overlap. Compared with no overlap patients, patients with any overlap had lower American Society of Anesthesiologists scores ( P  = .0018), less prior surgery ( P  < .0001), and less prior neurosurgery ( P  < .0001), though they tended to be older ( P  < .0001) and more likely in-patients ( P  = .0038). Any-overlap patients had decreased overall mortality (2.8% vs 4.5%; P  = .025), 30- to 90-d readmission rate (3.1% vs 5.5%; P  = .0034), 30- to 90-d reoperation rate (1.0% vs 2.0%; P  = .03), 30- to 90-d emergency room (ER) visit rate (2.1% vs 3.7%; P  = .018), and future surgery on index admission (2.8% vs 7.3%; P  < .0001). Multiple regression analysis validated noninferior outcomes for overlapping surgery, except for the association of increased future surgery on index admission with middle overlap (odds ratio 3.99; 95% confidence interval [1.91, 8.33]). CONCLUSION: Overlapping neurosurgery is associated with noninferior patient outcomes that may be driven by surgeon selection of healthier patients, regardless of specific overlap timing. Graphical Abstract: